Widespread impact of nucleosome remodelers on transcription at cis-regulatory elements - Benjamin J. Patty; Rinku Dhungana; Sarah J. Hainer (Cell Reports)
Summary: Nucleosome remodelers and regulatory factors collaborate to establish chromatin environments that control gene expression through cis-regulatory elements (CREs) such as promoters and enhancers, which drive transcription of mRNAs and CRE-associated non-coding RNAs (ncRNAs). Two CRE-associated ncRNAs include upstream antisense RNAs (uaRNAs) and enhancer RNAs (eRNAs). The role of remodelers in regulating CRE activity remains incompletely understood. Here, we investigated how SNF2-family remodelers regulate mRNA, eRNA, and uaRNA transcription in murine embryonic stem cells. We identified thousands of misregulated transcripts upon remodeler depletion and defined contributions of understudied remodelers. We find that paired mRNAs and eRNAs are co-regulated, while mRNAs and uaRNAs sharing a promoter are independently regulated by remodelers. Mechanistic studies reveal that CHD8 and SRCAP modulate transcription through canonical transcription factor and histone variant mechanisms, while other remodelers, including SMARCAL1, impact transcription indirectly by maintaining genomic stability. Our findings define classes of SNF2 remodelers in regulating the CRE-associated transcriptome.